Boothyord Dewhurst and Hitachi AEM design for assembly : a comparative study - Muhamad Farkhanif, Jamaluddin (2010)
Children's tricycles are typically used by children between the ages of two until four before they usually switch to a bicycle. This product is a good design to be commercialized. However, before releasing to the market, the product has to be cheap and good quality. Therefore, to achieve this goal, design for manufacture and assembly methodologies are used to evaluate the design of the product. Specifically, DFMA, which is Boothroyd-Dewhurst and Hitachi AEM, are used to evaluate the product. The strategy of evaluating the existing design is first to choose the available product in the market in order to solve a problem. The products choose were then disassembled into several families or sub-assemblies. This is for understanding how the parts functioning during normal operating mode. After that, each parts been critics and study if there is a chance for redesign. Finally, referring to result from current product based on Boothroyd-Dewhurst and Hitachi AEM method, the new parts designs are generated. Than the results for both analyses for improvement design are compared.